English Teacher’s Perception Towards Coaching Paradigm Implementation in Enhancing Learning Quality at SMP Negeri 2 Gunungsitoli Barat - Grace Marthini Waruwu; Yasminar Amaerita Telaumbanua; Afore Tahir Harefa; Yaredi Waruwu (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study investigates the English teacher's perception towards the coaching paradigm implementation in enhancing learning quality at SMP Negeri 2 Gunungsitoli Barat. Teacher perception is very important for making supervision work, and coaching is a new way for principals to guide teacher. The research employs a qualitative method with an English teacher and the school principal as the main sources of information. Data were collected using interviews, focusing on the English teacher's views and the steps taken by the principal as an effort to improve performance in order to enhance the quality of learning during the coaching, as well as observations of the coaching process. Results indicate that the teacher's feelings about the coaching changed from negative at the start to more positive over time. The results suggest that the coaching paradigm can be an effective way to guide English teacher if principal are patient and provide consistent support. Relevant implications for principal and teacher on how to create a more supportive and collaborative relationship to improve the quality of learning.